The Influence of Brand Image, Product Quality, and Price on the Purchase Decision of Ventela Shoe Products on E-Commerce Platforms - Trio Rahayu; Asep Irpan Alfauzi; Gilang Ramadhan (DEAL: International Journal of Economics and Business, 2024)
This study aims to analyze the influence of brand image, product quality, and price on purchasing decisionsfor Ventela shoe products on E-Commerce platforms, employing a quantitative research design. Theresearch focuses on consumers who utilize E-Commerce platforms, examining the variables of brand image,product quality, price, and purchasing decisions, with data collected from 83 respondents through astructured questionnaire measured on a Likert scale. The findings indicate that brand image and productquality have a negative and insignificant effect on purchasing decisions, while price demonstrates a positiveand significant influence. These results highlight the critical role of competitive pricing strategies in drivingconsumer purchasing decisions, while suggesting a need to reassess the impact of brand image and productquality within the E-Commerce context for Ventela shoe products.